(untitled) (Global Business Management Review (GBMR), 2025)
Franchise sector has significant contribution to local and global economic growth and development, yet franchisees’ long-term viability remains uncertain in times of global crisis. The current investigation examines the impact of market orientation, franchisor assistance, and government support on franchisee survival ability in Malaysia. Data was collected from 198 Malaysian franchisees using the survey approach. The analysis was carried out using structural equation modelling. The results demonstrated that market orientation (β=0.283, ρ<0.001), franchisor support (β=0.169, ρ<0.001), and government support (β=0.302, ρ<0.001), have significant positive impact on franchisee survival ability, indicating small to medium effect size FR (f2=0.022), GS (f2=0.073) and MO (f2=0.17). This study emphasized the importance of survival strategy, strategic networks and external alliances in times of global crisis, demonstrating their contribution to a resilient franchisee ecosystem. These findings fill gaps in the existing literature on sustainable franchising and provide feasible recommendations for policymakers, practitioners, and researchers to improve franchisee resilience and continuity. This research establishes a solid foundation for fostering continuity of franchisee in the face of economic and environmental uncertainty.